KEDUDUKAN DAN WEWENANG MAHKAMAH KONSTITUSI DALAM SISTEM HUKUM KETATANEGARAAN INDONESIA - Nanang Sri Darmadi (Unissula, 2012)
Fundamental changes in the 1945 is the amendment of Article 1 paragraph (2) as follows: